A boron nitride composite fiber material and a method for producing the same
Patent Information
- Application Number
- CN202311804402.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-26
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-12-26
AI Technical Summary
[0003]传统的轻质高效刚性耐高温、隔热材料一般以低导热、耐腐蚀、耐高温且性能稳定的石英纤维和氧化铝纤维为主要原材料,经湿法成型、高温烧结得到的多孔刚性隔热材料,该材料具有轻质、低导热、高强、耐高温的优异性能;但是现代飞行器超高声速、长航时等技术的发展,飞行器飞行过程中表面所承受的气动加热总量越来越大,现有的材料体系难以满足此服役环境下耐高温、抗烧蚀的使用要求
[0061]采用上一步的有益效果在于,通过模具一和/或模具二边侧设置的注浆孔向两层三级氮化硼纤维层之间注入隔热层骨架料浆,然后将所述模具一、模具二以及中间的物料进行冷冻处理,实现两层三级氮化硼纤维层的隔热层骨架料浆固化,然后经慢慢减压加热挥发溶剂、烧结成型,实现相邻的氮化硼纤维层之间隔热层包括大孔隙网状结构的氮化硅短切纤维;通过注入硅溶胶前驱体实现所述氮化硅短切纤维之间均匀的填充氧化硅气凝胶,且隔热层内部的氧化硅气凝胶与氮化硅短切纤维结合强度高,无明显缝隙与缺陷;同时实现隔热层氮化硅短切纤维与氮化硼纤维层内部的纤维结合强度高,明显增加了氮化硼纤维层与隔热层的强度,且整体材料的密度小、质量轻。
Abstract
Description
Technical Field
[0001] This invention relates to the field of boron nitride composite materials, and more specifically to the field of boron nitride composite fiber material and its preparation method. Background Technology
[0002] Lightweight, efficient, rigid, high-temperature resistant, and heat-insulating materials are widely needed in fields such as large-area thermal protection of new aircraft fuselages, insulation of civilian high-temperature kilns, and microwave smelting equipment.
[0003] Traditional lightweight, high-efficiency, rigid, high-temperature resistant, and heat-insulating materials are generally made from low thermal conductivity, corrosion resistance, high temperature resistance, and stable performance of quartz fiber and alumina fiber as the main raw materials. They are porous rigid heat-insulating materials obtained by wet molding and high-temperature sintering. These materials have excellent properties such as lightweight, low thermal conductivity, high strength, and high temperature resistance. However, with the development of technologies such as hypersonic speed and long endurance of modern aircraft, the total amount of aerodynamic heating that the surface of the aircraft is subjected to during flight is increasing. Existing material systems are difficult to meet the requirements of high temperature resistance and ablation resistance in this service environment.
[0004] Therefore, how to prepare a lightweight, efficient, rigid, high-temperature resistant, and heat-insulating material that can maintain good heat insulation performance and remain undeformed at temperatures above 1500℃ has become a pressing problem to be solved in this field. Summary of the Invention
[0005] The purpose of this invention is to provide a boron nitride composite fiber material and its preparation method, achieving a boron nitride composite fiber material with a density of 0.1–0.5 g / cm³. 3 It still has good heat insulation performance at temperatures above 1500℃ and does not deform.
[0006] According to one aspect of the present invention, a boron nitride composite fiber material is provided, comprising a plurality of boron nitride fiber layers; a heat insulation layer is provided between two adjacent fiber layers;
[0007] The boron nitride fiber layer comprises interlaced boron nitride fibers; the spaces between the interlaced boron nitride fibers are filled with interlaced silicon nitride short fibers.
[0008] The surface of the boron nitride fiber is coated with silicon oxide, and the surface of the silicon nitride short fiber is coated with silicon oxide; the interface between the boron nitride fiber layer and the heat insulation layer is provided with a boron nitride layer attached to the outermost surface of the boron nitride fiber.
[0009] The thermal insulation layer comprises silica aerogel. Preferably, the surface of the boron nitride fiber interlacing points is coated with silicon nitride, and silicon nitride is attached to the interlacing points of the boron nitride short fibers.
[0010] The advantages of this invention over the prior art are as follows: Through several layers of boron nitride fiber, and with a heat insulation layer between adjacent fiber layers, the boron nitride fiber layer on its outer surface can withstand temperatures up to 2000°C or higher in an oxygen-free environment. This facilitates achieving a temperature resistance of approximately 2000°C in an oxygen-free environment. Furthermore, the presence of a heat insulation layer in the middle, including silica aerogel, effectively avoids the problem of reduced thermal conductivity due to aerogel structure damage at external temperatures exceeding 1500°C. Therefore, the finished material retains excellent heat insulation performance even in external high-temperature environments exceeding 1500°C.
[0011] The boron nitride fiber layer comprises interlaced boron nitride fibers, with interlaced silicon nitride short fibers filling the gaps between the interlaced boron nitride fibers. This achieves high strength and toughness for the outer boron nitride fiber layer. Furthermore, the interface between the boron nitride fiber layer and the insulation layer has an outermost boron nitride layer attached, enabling the boron nitride fiber layer to have controllable porosity with a pore gradient. The porosity of the boron nitride fiber layer gradually decreases from the outside to the inside, with high porosity further away from the insulation layer and decreasing towards the insulation layer. This results in high thermal insulation performance for the boron nitride fiber layer itself and effectively blocks external gases from entering the insulation layer, further preventing the insulation layer from being directly affected by high-temperature external gases and causing structural changes.
[0012] Most importantly, by attaching silicon oxide to the surface of the boron nitride fibers and the short silicon nitride fibers, the problem of oxidation of the boron nitride fibers and short silicon nitride fibers in high-temperature and oxygen-containing environments is avoided. This also facilitates the controllable and achievable change in the porosity gradient of the boron nitride fiber layer. Because although the spatial structure of silicon oxide does not change in high-temperature environments above 1500°C and in oxygen-containing environments, it will not be oxidized or decomposed. Therefore, it will not fundamentally change the structure of silicon oxide attached to the surface of boron nitride fibers and short silicon nitride fibers in high-temperature environments above 1500°C and in oxygen-containing environments. This effectively isolates the boron nitride fibers and short silicon nitride fibers from air and prevents them from being oxidized.
[0013] By attaching silicon oxide to the surface of the boron nitride fibers and the surface of the silicon nitride short fibers, the connection strength between the fibers is increased, thereby stabilizing the fiber network structure inside the finished material and improving the compressive strength of the finished material.
[0014] Furthermore, the boron nitride composite fiber material has a content of 0.1–0.5 g / cm³. 3The compressive strength is 1.2 to 5 MPa, the temperature resistance is ≥2000℃, and the thermal conductivity at 1500℃ is 0.036 to 0.048 W / (m·K); preferably, the thermal conductivity at 1500℃ is 0.036 to 0.04 W / (m·K).
[0015] Furthermore, the boron nitride composite fiber material comprises two boron nitride fiber layers; the length of the boron nitride fiber is 5-10 mm; and the length of the silicon nitride fiber is 0.2-3 mm.
[0016] According to one aspect of the present invention, a method for preparing boron nitride composite fiber material is provided, characterized by comprising the following steps:
[0017] The boron nitride fibers were modified to obtain modified boron nitride fibers.
[0018] Silicon nitride short fibers were modified to obtain modified silicon nitride short fibers;
[0019] A primary boron nitride fiber layer preform with a mesh structure was prepared by modifying boron nitride fibers.
[0020] The modified silicon nitride short fibers are added into the mesh pores of the primary boron nitride fiber layer preform to obtain the secondary boron nitride fiber layer preform.
[0021] One side of the secondary boron nitride fiber layer preform is impregnated with a boronazane precursor solution, and then the tertiary boron nitride fiber layer preform is obtained by vacuum treatment and drying.
[0022] The boronazine precursor in the tertiary boron nitride fiber layer preform is pyrolyzed to obtain a quaternary boron nitride fiber layer preform.
[0023] Several prefabricated boron nitride fiber layers of grade 4 are placed in parallel, with an accommodating space between adjacent boron nitride fiber layers of grade 4;
[0024] A silica sol precursor is injected into the accommodating space, while the side of the quadrature boron nitride fiber layer away from the accommodating space is in a negative pressure environment. Then, the silica sol precursor is sol-gelled to obtain a boron nitride composite fiber material precursor.
[0025] The boron nitride composite fiber material precursor is replaced and critically dried to obtain the boron nitride composite fiber material.
[0026] The beneficial effect of this invention compared with the prior art is that, by preparing a primary boron nitride fiber layer preform with a mesh structure through modified boron nitride fibers, the boron nitride fiber layer includes boron nitride fibers with silicon oxide attached to the surface;
[0027] By adding the modified silicon nitride short fibers into the mesh pores of the primary boron nitride fiber layer preform, the boron nitride fiber layer includes the silicon nitride short fibers with silicon oxide attached to their surface; and the silicon nitride short fibers fill the mesh spaces formed by the interlaced arrangement of boron nitride fibers.
[0028] A quaternary boron nitride fiber layer preform is obtained by pyrolyzing the boronazane precursor in the tertiary boron nitride fiber layer preform; and several quaternary boron nitride fiber layer preforms are placed in parallel with a space between adjacent quaternary boron nitride fiber layers, and a silica sol precursor is injected into the space; a heat insulation layer including silica aerogel is provided between adjacent fiber layers, and a boron nitride layer attached to the outermost surface of the boron nitride fiber is provided at the interface between the boron nitride fiber layer and the heat insulation layer.
[0029] Meanwhile, by first modifying boron nitride fibers and silicon nitride short fibers before fabricating boron nitride fiber layer preforms, the problem of filling the boron nitride fiber layer preforms with excess silicon oxide is avoided, thus avoiding the problems of uncontrollable porosity of boron nitride fiber layers and reduced thermal coefficient and reduced surface high temperature resistance.
[0030] Meanwhile, boron nitride has excellent wave transmission properties, making it well-suited for use in radome applications.
[0031] Furthermore, the preparation process of the modified boron nitride fiber is as follows: preparing a modification solution; impregnating the boron nitride fiber with the modification solution; and then drying the boron nitride fiber to obtain the modified boron nitride fiber.
[0032] The modified solution comprises silica sol, organic binder, and water in a mass ratio of (30-60):(10-20):(80-100);
[0033] The preparation process of the modified silicon nitride short fiber is as follows: preparing a modification solution; impregnating the silicon nitride short fiber with the modification solution; and then drying the silicon nitride short fiber to obtain the modified silicon nitride short fiber.
[0034] The organic binder includes one or more of starch, PEO, cellulose, and polyacrylic acid;
[0035] The boron nitride fiber has a length of 5–10 mm; the silicon nitride fiber has a length of 0.2–3 mm.
[0036] The drying temperature is 80–150°C, and the drying time is 0.5–2.5 h.
[0037] The beneficial effect of the previous step is that it achieves the modification of boron nitride fibers, and after modification, silicon oxide is attached to the surface of the boron nitride fibers; it also achieves the modification of silicon nitride short fibers, and after modification, silicon oxide is attached to the surface of the silicon nitride short fibers.
[0038] By attaching silicon oxide to the fiber surface, the boron nitride fiber and silicon nitride chopped fiber are isolated from air to achieve oxidation resistance. At the same time, it is beneficial for the boron alkane precursor attached to the surface of the subsequent cross-point to react with silicon oxide during the cracking process to generate silicon nitride, which is then attached to the surface of the cross-point.
[0039] By using boron nitride fibers with a length of 5–10 mm and silicon nitride fibers with a length of 0.2–3 mm, silicon nitride fibers are dispersed between the pores of boron nitride fibers, enabling controllable and gradient changes in the porosity of the boron nitride fiber layer. This allows the porosity to gradually decrease from the outside to the inside while meeting the requirements of high temperature resistance. Additionally, the use of silicon nitride helps to increase the bonding strength with the heat insulation layer.
[0040] Further, the modified boron nitride fibers are dispersed in a solvent to obtain a primary boron nitride fiber layer slurry; the primary boron nitride fiber layer slurry is filtered through a first filter screen to obtain a primary boron nitride fiber layer preform; the solid content of the primary boron nitride fiber layer slurry is 30-40%.
[0041] The preparation process of the secondary boron nitride fiber layer preform includes the following steps: dispersing the modified silicon nitride short fibers in a solvent to obtain a secondary boron nitride fiber layer slurry; adding the secondary boron nitride fiber layer slurry into a first filter screen containing a primary boron nitride fiber layer preform; and filtering to obtain the secondary boron nitride fiber layer preform.
[0042] The solid content of the secondary boron nitride fiber layer slurry is 40-60%.
[0043] The advantage of the previous step is that it enables controllable changes in the pore gradient within the boron nitride fiber layer preform.
[0044] Furthermore, the preparation process of the tertiary boron nitride fiber layer preform includes: preparing a boron alkane precursor solution, impregnating one side of the secondary boron nitride fiber layer preform with the boron alkane precursor solution under vacuum, and then drying it at a temperature of 75-85°C under negative pressure to obtain the tertiary boron nitride fiber layer preform;
[0045] The boronazine precursor solution has a mass fraction of 20-50%; the boronazine precursor solution includes monomeric cycloborazine or polymeric polyborazine.
[0046] The beneficial effect of the previous step is that it enables the boron nitride fiber layer preform to have boron nitride precursors on one side and in some pores.
[0047] Furthermore, the preparation process of the four-stage boron nitride fiber layer preform is as follows: the three-stage boron nitride fiber layer preform is heated in an atmosphere of ammonia and nitrogen, with the temperature increased from room temperature to 280–320°C at a rate of 0.3–0.6°C / min; from 280–320°C to 580–620°C at a rate of 0.5–2°C / min; from 580–620°C to 990–1000°C at a rate of 5–10°C / min, and held at 990–1000°C for 1–3 hours; the total flow rate of ammonia and nitrogen is 0.15–0.25 m³ / min. 3 / h;
[0048] Then, heating is carried out in a nitrogen atmosphere, with the temperature increased from 990–1000℃ to 1550–1650℃ at a heating rate of 5.5–6.5℃ / min, and held at 1550–1650℃ for 1.8–2.2 h; the nitrogen flow rate is 0.15–0.25 m³ / min. 3 / h;
[0049] The beneficial effect of the previous step is that it enables the boron alkane precursor to be decomposed into boron nitride on one side and in some pores of the three-stage boron nitride fiber layer preform, while increasing the sintering strength between fibers. By passing a certain amount of nitrogen gas as a carrier gas, it is beneficial to remove the decomposition byproducts to obtain boron nitride. Continuing to pass nitrogen gas in the subsequent process avoids the decomposition of boron nitride during high-temperature ceramicization.
[0050] Furthermore, the preparation process of the boron nitride composite fiber material precursor includes placing the two-layer quadrature boron nitride fiber layer preforms in mold one and mold two respectively, with mold one and mold two arranged opposite to each other, forming a closed accommodating cavity between the two quadrature boron nitride fiber layer preforms, injecting the silica sol precursor into the accommodating cavity through the grouting holes provided on the side of mold one and / or mold two, and then placing mold one and mold two in a negative pressure environment;
[0051] The two boron nitride fiber layer preforms are impregnated with boronazane precursor solution on opposite sides;
[0052] Then, the silica sol precursor is sol-gelled to obtain the boron nitride composite fiber material precursor.
[0053] The beneficial effect of the previous step is that a silica aerogel insulation layer is connected between adjacent boron nitride fiber layers, and a boron nitride layer attached to the outermost surface of the boron nitride fiber is provided at the interface between the boron nitride fiber layer and the insulation layer.
[0054] Furthermore, the modified silicon nitride short fibers are dispersed in a solvent to obtain a heat insulation layer skeleton slurry; the solid content of the heat insulation layer skeleton slurry is 15-20%; the solvent is water;
[0055] Before ammonia is produced, the boronazane precursor of the three-stage boron nitride fiber layer preform is cracked. The two-layer boron nitride fiber layer preforms are placed in mold one and mold two, respectively, with mold one and mold two facing each other to form a sealed cavity between the two preforms. Then, the heat insulation layer skeleton slurry is injected between the two layers of boron nitride fiber layers through the slurry injection holes on the sides of mold one and / or mold two. Finally, mold one, mold two, and the material in between are frozen.
[0056] After freezing, the material undergoes a first-stage heating treatment in a nitrogen atmosphere; then a second-stage heating treatment is performed in an ammonia and nitrogen atmosphere; resulting in two layers of four-level boron nitride fiber layers with a three-dimensional mesh insulation layer skeleton sandwiched in between; the three-dimensional mesh insulation layer skeleton includes three-dimensional silicon nitride fibers; the thickness of the three-dimensional mesh insulation layer skeleton is 0.5-1.5 cm.
[0057] In a negative pressure environment, the silica sol precursor, boron nitride composite fiber material precursor, is injected into the three-dimensional mesh insulation layer skeleton sandwiched between the two layers of boron nitride fiber layers through the grouting holes set on the sides of mold one and / or mold two.
[0058] The first stage of the heating process includes raising the temperature from room temperature to 80-120°C under negative pressure, at a rate of 0.3-0.6°C / min.
[0059] The second stage of the heating process includes, in an atmosphere of ammonia and nitrogen, heating from 80–120°C to 280–320°C at a rate of 0.3–0.6°C / min; heating from 280–320°C to 580–620°C at a rate of 0.5–2°C / min; heating from 580–620°C to 990–1000°C at a rate of 5–10°C / min; and holding at 990–1000°C for 1–3 hours; the total flow rate of ammonia and nitrogen is 0.15–0.25 m³ / min. 3 / h;
[0060] Then, heating is carried out in a nitrogen atmosphere, with the temperature increased from 990–1000℃ to 1550–1650℃ at a heating rate of 5.5–6.5℃ / min, and held at 1550–1650℃ for 1.8–2.2 h; the nitrogen flow rate is 0.15–0.25 m³ / min. 3 / h.
[0061] The beneficial effects of the previous step are that the heat insulation layer skeleton slurry is injected into the space between the two layers of tertiary boron nitride fiber through the injection holes on the sides of mold one and / or mold two. Then, mold one, mold two, and the material in between are frozen to solidify the heat insulation layer skeleton slurry of the two layers of tertiary boron nitride fiber. Then, the solvent is evaporated by slow depressurization heating and sintering, so that the heat insulation layer between adjacent boron nitride fiber layers includes chopped silicon nitride fibers with a large-pore network structure. By injecting a silica sol precursor, silica aerogel is uniformly filled between the chopped silicon nitride fibers, and the silica aerogel inside the heat insulation layer has a high bonding strength with the chopped silicon nitride fibers, with no obvious gaps or defects. At the same time, the bonding strength between the chopped silicon nitride fibers in the heat insulation layer and the fibers inside the boron nitride fiber layer is high, which significantly increases the strength of the boron nitride fiber layer and the heat insulation layer, and the overall material has a low density and light weight. Detailed Implementation
[0062] To better understand the technical solution of the present invention, the present invention will be further described below with reference to specific embodiments.
[0063] Example 1:
[0064] One aspect of this embodiment provides a boron nitride composite fiber material, comprising two boron nitride fiber layers; a heat insulation layer is provided between adjacent fiber layers.
[0065] The boron nitride fiber layer comprises interlaced boron nitride fibers; the spaces between the interlaced boron nitride fibers are filled with interlaced short silicon nitride fibers; the length of the boron nitride fibers is 7 mm; the length of the silicon nitride fibers is 1.6 mm.
[0066] The surface of the boron nitride fiber is coated with silicon oxide, and the surface of the silicon nitride short fiber is coated with silicon oxide; the interface between the boron nitride fiber layer and the heat insulation layer is provided with a boron nitride layer attached to the outermost surface of the boron nitride fiber; the heat insulation layer includes silica aerogel;
[0067] The boron nitride composite fiber material is 0.3 g / cm³. 3 It has a compressive strength of 3MPa, a temperature resistance of ≥2000℃, and a thermal conductivity of 0.037W / (m·K) at 1500℃; the thermal conductivity is 0.039W / (m·K) at 1500℃.
[0068] Another aspect of this embodiment provides a method for preparing boron nitride composite fiber material, including the following steps: modifying the boron nitride fiber to obtain modified boron nitride fiber;
[0069] The preparation process of the modified boron nitride fiber is as follows: preparing a modification solution; impregnating the boron nitride fiber with the modification solution; and then drying the boron nitride fiber to obtain the modified boron nitride fiber.
[0070] The modified solution comprises silica sol, organic binder, and water in a mass ratio of 45:15:90; the boron nitride fiber has a length of 7 mm.
[0071] Silicon nitride short fibers are modified to obtain modified silicon nitride short fibers. The preparation process of the modified silicon nitride short fibers is as follows: a modification solution is prepared; the silicon nitride short fibers are impregnated with the modification solution, and then the silicon nitride short fibers are dried to obtain the modified silicon nitride short fibers; the length of the silicon nitride fibers is 1.6 mm.
[0072] The organic binder includes polyacrylic acid; the drying temperature is 120°C, and the drying time is 1.5 hours.
[0073] A primary boron nitride fiber layer preform with a mesh structure was prepared by modifying boron nitride fibers; the modified boron nitride fibers were dispersed in a solvent to obtain a primary boron nitride fiber layer slurry; the primary boron nitride fiber layer slurry was filtered through a first filter screen to obtain the primary boron nitride fiber layer preform; the solid content of the primary boron nitride fiber layer slurry was 35%.
[0074] The modified silicon nitride short fibers are added into the mesh pores of the primary boron nitride fiber layer preform to obtain the secondary boron nitride fiber layer preform. The preparation process of the secondary boron nitride fiber layer preform includes the following steps: dispersing the modified silicon nitride short fibers in a solvent to obtain a secondary boron nitride fiber layer slurry; adding the secondary boron nitride fiber layer slurry into a first filter screen containing the primary boron nitride fiber layer preform, and filtering to obtain the secondary boron nitride fiber layer preform.
[0075] The solid content of the secondary boron nitride fiber layer slurry is 50%.
[0076] A secondary boron nitride fiber layer preform is impregnated with a boronazine precursor solution on one side, and then dried under vacuum to obtain a tertiary boron nitride fiber layer preform. The preparation process of the tertiary boron nitride fiber layer preform includes: preparing a boronazine precursor solution, impregnating one side of the secondary boron nitride fiber layer preform with the boronazine precursor solution under vacuum, and then drying it at 80°C under negative pressure to obtain the tertiary boron nitride fiber layer preform.
[0077] The borazine precursor solution has a mass fraction of 25%; the borazine precursor solution includes the monomer cycloborane.
[0078] The boronazine precursor in the tertiary boron nitride fiber layer preform was pyrolyzed to obtain a quaternary boron nitride fiber layer preform. The tertiary boron nitride fiber layer preform was then heated in an ammonia and nitrogen atmosphere, with the temperature increased from room temperature to 290°C at a rate of 0.55°C / min; from 290°C to 590°C at a rate of 0.19°C / min; and from 590°C to 991°C at a rate of 9.5°C / min, and held at 991°C for 1.2 hours. The total flow rate of ammonia and nitrogen was 0.16 m³ / min. 3 / h;
[0079] Then, heating was carried out in a nitrogen atmosphere, with the temperature increased from 990–1000℃ to 1550–1650℃ at a heating rate of 5.5–6.5℃ / min, and the temperature was held at 1550–1650℃ for 1.8–2.2 hours; the nitrogen flow rate was 0.16 m³ / min. 3 / h;
[0080] Two quadri-level boron nitride fiber layer preforms are placed in parallel, with an accommodating space between adjacent quadri-level boron nitride fiber layers; the preparation process of the boron nitride composite fiber material precursor includes placing the two quadri-level boron nitride fiber layer preforms in mold one and mold two respectively, with mold one and mold two arranged opposite to each other, forming a closed accommodating cavity between the two quadri-level boron nitride fiber layer preforms, injecting silica sol precursor into the accommodating cavity through grouting holes provided on the sides of mold one and / or mold two, and then placing mold one and mold two in a negative pressure environment;
[0081] The two boron nitride fiber layer preforms are impregnated with boronazane precursor solution on opposite sides;
[0082] Then, the silica sol precursor is sol-gelled to obtain the boron nitride composite fiber material precursor.
[0083] A silica sol precursor is injected into the accommodating space, while the side of the quaternary boron nitride fiber layer away from the accommodating space is placed under negative pressure. The silica sol precursor is then sol-gelled to obtain a boron nitride composite fiber material precursor. The boron nitride composite fiber material precursor is then replaced and critically dried to obtain the boron nitride composite fiber material.
[0084] Example 2:
[0085] The same content as in Example 1 will not be repeated here; the different aspects of this embodiment compared to Example 1 are as follows:
[0086] One aspect of this embodiment provides a boron nitride composite fiber material, wherein the thermal insulation layer comprises silica aerogel and a three-dimensional mesh thermal insulation layer skeleton; the three-dimensional mesh thermal insulation layer skeleton comprises three-dimensional silicon nitride fibers; the thickness of the three-dimensional mesh thermal insulation layer skeleton is 1 cm; the silica aerogel is uniformly dispersed within the three-dimensional mesh thermal insulation layer skeleton; the surface of the intersection points of the boron nitride fibers is coated with silicon nitride, and silicon nitride is attached to the intersection points of the boron nitride short fibers; the boron nitride composite fiber material comprises two boron nitride fiber layers; the length of the boron nitride fibers is 9 mm; the length of the silicon nitride fibers is 2.5 mm;
[0087] The boron nitride composite fiber material is 0.15 g / cm³. 3 It has a compressive strength of 2.8 MPa, a temperature resistance of ≥2000℃, and a thermal conductivity of 0.042 W / (m·K) at 1500℃; the thermal conductivity is 0.045 W / (m·K) at 1500℃.
[0088] Another aspect of this embodiment provides a method for preparing boron nitride composite fiber material, which further includes preparing a heat insulation layer skeleton slurry, specifically including the following steps: dispersing the modified silicon nitride short fibers in a solvent to obtain a heat insulation layer skeleton slurry; the solid content of the heat insulation layer skeleton slurry is 16%; the solvent is water;
[0089] Before ammonia is produced, the boronazane precursor of the three-stage boron nitride fiber layer preform is cracked. The two-layer boron nitride fiber layer preforms are placed in mold one and mold two, respectively, with mold one and mold two facing each other to form a sealed cavity between the two preforms. Then, the heat insulation layer skeleton slurry is injected between the two layers of boron nitride fiber layers through the slurry injection holes on the sides of mold one and / or mold two. Finally, mold one, mold two, and the material in between are frozen.
[0090] After freezing, the material undergoes a first-stage heating treatment in a nitrogen atmosphere; then a second-stage heating treatment is performed in an ammonia and nitrogen atmosphere; resulting in two layers of boron nitride fiber with a three-dimensional mesh insulation layer skeleton sandwiched in the middle; the three-dimensional mesh insulation layer skeleton includes three-dimensional silicon nitride fiber; the thickness of the three-dimensional mesh insulation layer skeleton is 1 cm;
[0091] In a negative pressure environment, the silica sol precursor, boron nitride composite fiber material precursor, is injected into the three-dimensional mesh insulation layer skeleton sandwiched between the two layers of boron nitride fiber layers through the grouting holes set on the sides of mold one and / or mold two.
[0092] The first stage of the heating process includes heating from room temperature to 100°C under negative pressure at a rate of 0.45°C / min.
[0093] The second stage of the heating process includes, in an atmosphere of ammonia and nitrogen, heating from 100°C to 300°C at a rate of 0.45°C / min; heating from 300°C to 600°C at a rate of 1.3°C / min; heating from 600°C to 995°C at a rate of 7.5°C / min; and holding at 995°C for 2 hours; the total flow rate of ammonia and nitrogen is 0.2 m³ / min. 3 / h;
[0094] Then, heating was carried out in a nitrogen atmosphere, from 995℃ to 1600℃ at a heating rate of 6℃ / min, and the temperature was held at 1600℃ for 2 hours; the nitrogen flow rate was 0.2 m³ / min. 3 / h.
[0095] The modified solution comprises silica sol, organic binder, and water in a mass ratio of 35:12:85; the boron nitride fiber has a length of 9 mm.
[0096] The silicon nitride fiber has a length of 2.5 mm; the primary boron nitride fiber layer slurry has a solid content of 32%.
[0097] The organic binder includes PEO and cellulose;
[0098] The drying temperature is 140℃ and the drying time is 2 hours.
[0099] The solid content of the secondary boron nitride fiber layer slurry is 43%.
[0100] A boronazine precursor solution is prepared, and the secondary boron nitride fiber layer preform is impregnated with the boronazine precursor solution under vacuum, and then dried at 78°C under negative pressure to obtain the tertiary boron nitride fiber layer preform; the mass fraction of the boronazine precursor solution is 35%; the boronazine precursor solution includes the polymer polyborazine.
[0101] Example 3:
[0102] The same content as in Example 1 will not be repeated here; the different aspects of this embodiment compared to Example 1 are as follows:
[0103] One aspect of this embodiment provides a boron nitride composite fiber material, wherein the thermal insulation layer comprises silica aerogel and a three-dimensional mesh thermal insulation layer skeleton; the three-dimensional mesh thermal insulation layer skeleton comprises three-dimensional silicon nitride fibers; the thickness of the three-dimensional mesh thermal insulation layer skeleton is 0.8 cm; the silica aerogel is uniformly dispersed within the three-dimensional mesh thermal insulation layer skeleton; the surface of the intersection points of the boron nitride fibers is coated with silicon nitride, and silicon nitride is attached to the intersection points of the boron nitride short fibers; the boron nitride composite fiber material comprises two boron nitride fiber layers; the length of the boron nitride fibers is 6 mm; the length of the silicon nitride fibers is 0.5 mm;
[0104] The boron nitride composite fiber material is 0.35 g / cm³. 3 It has a compressive strength of 4.5 MPa, a temperature resistance of ≥2000℃, and a thermal conductivity of 0.038 W / (m·K) at 1500℃; the thermal conductivity is 0.039 W / (m·K) at 1500℃.
[0105] Another aspect of this embodiment provides a method for preparing boron nitride composite fiber material, which further includes preparing a heat insulation layer skeleton slurry, specifically including the following steps: dispersing the modified silicon nitride short fibers in a solvent to obtain a heat insulation layer skeleton slurry; the solid content of the heat insulation layer skeleton slurry is 18%; the solvent is water;
[0106] Before ammonia is produced, the boronazane precursor of the three-stage boron nitride fiber layer preform is cracked. The two-layer boron nitride fiber layer preforms are placed in mold one and mold two, respectively, with mold one and mold two facing each other to form a sealed cavity between the two preforms. Then, the heat insulation layer skeleton slurry is injected between the two layers of boron nitride fiber layers through the slurry injection holes on the sides of mold one and / or mold two. Finally, mold one, mold two, and the material in between are frozen.
[0107] After freezing, the material undergoes a first-stage heating treatment in a nitrogen atmosphere; then a second-stage heating treatment is performed in an ammonia and nitrogen atmosphere; resulting in two layers of four-level boron nitride fiber layers with a three-dimensional mesh insulation layer skeleton sandwiched in the middle; the three-dimensional mesh insulation layer skeleton includes three-dimensional silicon nitride fibers; the thickness of the three-dimensional mesh insulation layer skeleton is 0.8 cm;
[0108] In a negative pressure environment, the silica sol precursor, boron nitride composite fiber material precursor, is injected into the three-dimensional mesh insulation layer skeleton sandwiched between the two layers of boron nitride fiber layers through the grouting holes set on the sides of mold one and / or mold two.
[0109] The first stage of the heating process includes heating from room temperature to 85°C under negative pressure, at a heating rate of 0.35°C / min.
[0110] The second stage of the heating process includes, in an atmosphere of ammonia and nitrogen, heating from 115°C to 310°C at a rate of 0.35°C / min; heating from 310°C to 610°C at a rate of 0.7°C / min; heating from 610°C to 998°C at a rate of 6°C / min; and holding at 998°C for 1–3 hours; the total flow rate of ammonia and nitrogen is 0.22 m³ / min. 3 / h;
[0111] Then, heating was carried out in a nitrogen atmosphere, from 998℃ to 1630℃ at a heating rate of 6.2℃ / min, and the temperature was held at 1630℃ for 2.1 hours; the nitrogen flow rate was 0.22 m³ / min. 3 / h.
[0112] The modified solution comprises silica sol, organic binder, and water in a mass ratio of 55:18:95; the boron nitride fiber has a length of 6 mm.
[0113] The silicon nitride fiber has a length of 0.5 mm; the primary boron nitride fiber layer slurry has a solid content of 38%.
[0114] The organic binder includes PEO and polyacrylic acid;
[0115] The drying temperature is 85℃ and the drying time is 0.8h.
[0116] The solid content of the secondary boron nitride fiber layer slurry is 58%.
[0117] A boronazine precursor solution was prepared, and the secondary boron nitride fiber layer preform was impregnated with the boronazine precursor solution under vacuum, and then dried at 82°C under negative pressure to obtain the tertiary boron nitride fiber layer preform; the mass fraction of the boronazine precursor solution was 46%; the boronazine precursor solution included the polymer polyborazine.
[0118] The above description is merely a preferred embodiment of this application and an explanation of the technical principles employed. Those skilled in the art should understand that the scope of the invention involved in this application is not limited to the technical solutions formed by specific combinations of the above-described technical features, but should also cover other technical solutions formed by arbitrary combinations of the above-described technical features or their equivalents without departing from the inventive concept. For example, the above-described features have similar functions to (but are not limited to) those disclosed in this application.
Claims
1. A boron nitride composite fiber material, characterized in that, It includes several layers of boron nitride fiber; a heat insulation layer is provided between two adjacent fiber layers; The boron nitride fiber layer comprises interlaced boron nitride fibers; the spaces between the interlaced boron nitride fibers are filled with interlaced silicon nitride short fibers. The surface of the boron nitride fiber is coated with silicon oxide, and the surface of the silicon nitride short fiber is coated with silicon oxide. The interface between the boron nitride fiber layer and the heat insulation layer is provided with a boron nitride layer attached to the outermost surface of the boron nitride fiber. The insulation layer comprises silica aerogel.
2. The boron nitride composite fiber material according to claim 1, characterized in that, The density of the boron nitride composite fiber material is 0.1~0.5 g / cm³. 3 It has a compressive strength of 1.2~5MPa, a temperature resistance of ≥2000℃, and a thermal conductivity of 0.036~0.048W / (m·K) at 1500℃.
3. The boron nitride composite fiber material according to claim 1, characterized in that, The boron nitride composite fiber material comprises two layers of boron nitride fibers. The boron nitride fiber has a length of 5-10 mm; the silicon nitride fiber has a length of 0.2-3 mm.
4. A method for preparing the boron nitride composite fiber material according to claim 1, characterized in that, Includes the following steps, Boron nitride fibers were modified to obtain modified boron nitride fibers. Silicon nitride short fibers were modified to obtain modified silicon nitride short fibers; A primary boron nitride fiber layer preform with a mesh structure was prepared by modifying boron nitride fibers. The modified silicon nitride short fibers are added into the mesh pores of the primary boron nitride fiber layer preform to obtain the secondary boron nitride fiber layer preform. One side of the secondary boron nitride fiber layer preform is impregnated with a boronazane precursor solution, and then the tertiary boron nitride fiber layer preform is obtained by vacuum treatment and drying. The boronazine precursor in the tertiary boron nitride fiber layer preform is pyrolyzed to obtain a quaternary boron nitride fiber layer preform. Several prefabricated boron nitride fiber layers of grade 4 are placed in parallel, with an accommodating space between adjacent boron nitride fiber layers of grade 4; A silica sol precursor is injected into the accommodating space, while the side of the quadrature boron nitride fiber layer away from the accommodating space is in a negative pressure environment. Then, the silica sol precursor is sol-gelled to obtain a boron nitride composite fiber material precursor. The boron nitride composite fiber material precursor is subjected to displacement and critical drying to obtain the boron nitride composite fiber material. The preparation process of the modified boron nitride fiber is as follows: preparing a modification solution; Boron nitride fibers are impregnated with a modified solution and then dried to obtain the modified boron nitride fibers. The modified solution comprises silica sol, organic binder, and water in a mass ratio of (30~60):(10~20):(80~100); The preparation process of the modified silicon nitride short fibers is as follows: preparing a modification solution; Silicon nitride short fibers are impregnated with a modified solution and then dried to obtain the modified silicon nitride short fibers. The organic binder includes one or more of starch, PEO, cellulose, and polyacrylic acid; The boron nitride fiber has a length of 5-10 mm; the silicon nitride fiber has a length of 0.2-3 mm. The drying temperature is 80~150℃, and the drying time is 0.5~2.5h.
5. The method for preparing boron nitride composite fiber material according to claim 4, characterized in that, The preparation process of the primary boron nitride fiber layer preform includes the following steps: dispersing the modified boron nitride fibers in a solvent to obtain a primary boron nitride fiber layer slurry; filtering the primary boron nitride fiber layer slurry through a first filter screen to obtain the primary boron nitride fiber layer preform; the solid content of the primary boron nitride fiber layer slurry is 30-40%. The preparation process of the secondary boron nitride fiber layer preform includes the following steps: dispersing the modified silicon nitride short fibers in a solvent to obtain a secondary boron nitride fiber layer slurry; The secondary boron nitride fiber layer slurry is added to the first filter screen containing the primary boron nitride fiber layer preform, and after filtration, the secondary boron nitride fiber layer preform is obtained. The solid content of the secondary boron nitride fiber layer slurry is 40-60%.
6. The method for preparing boron nitride composite fiber material according to claim 4, characterized in that, The preparation process of the tertiary boron nitride fiber layer preform includes: preparing a boron alkane precursor solution, impregnating one side of the tertiary boron nitride fiber layer preform with the boron alkane precursor solution under vacuum, and then drying it at a temperature of 75~85°C under negative pressure to obtain the tertiary boron nitride fiber layer preform. The borazine precursor solution has a mass fraction of 20-50%; the borazine precursor solution includes monomeric cycloborazine or polymeric polyborazine.
7. The method for preparing boron nitride composite fiber material according to claim 4, characterized in that, The preparation process of the four-stage boron nitride fiber layer preform is as follows: the three-stage boron nitride fiber layer preform is heated in an atmosphere of ammonia and nitrogen, with the temperature increased from room temperature to 280~320℃ at a rate of 0.3~0.6℃ / min; from 280~320℃ to 580~620℃ at a rate of 0.5~2℃ / min; from 580~620℃ to 990~1000℃ at a rate of 5~10℃ / min, and held at 990~1000℃ for 1~3 hours; the total flow rate of ammonia and nitrogen is 0.15~0.25 m³ / min. 3 / h; Then, heating is carried out in a nitrogen atmosphere, with the temperature increased from 990~1000℃ to 1550~1650℃ at a heating rate of 5.5~6.5℃ / min, and held at 1550~1650℃ for 1.8~2.2h; the nitrogen flow rate is 0.15~0.25m³ / min. 3 / h.
8. The method for preparing boron nitride composite fiber material according to claim 4, characterized in that, The preparation process of the boron nitride composite fiber material precursor includes placing the two-layer quadrature boron nitride fiber layer preforms in mold one and mold two respectively, with mold one and mold two arranged opposite to each other, forming a closed accommodating cavity between the two quadrature boron nitride fiber layer preforms, injecting the silica sol precursor into the accommodating cavity through the grouting holes provided on the side of mold one and / or mold two, and then placing mold one and mold two in a negative pressure environment; The two boron nitride fiber layer preforms are impregnated with boronazane precursor solution on opposite sides; Then, the silica sol precursor is sol-gelled to obtain the boron nitride composite fiber material precursor.
9. The method for preparing boron nitride composite fiber material according to claim 4, characterized in that, It also includes the preparation of a heat insulation layer skeleton slurry, specifically comprising the following steps: dispersing the modified silicon nitride short fibers in a solvent to obtain a heat insulation layer skeleton slurry; the solid content of the heat insulation layer skeleton slurry is 15-20%; the solvent is water; Before pyrolyzing the boronazane precursor of the three-stage boron nitride fiber layer preform, the two-stage boron nitride fiber layer preforms are placed in mold one and mold two respectively, with mold one and mold two facing each other to form a sealed cavity between the two three-stage boron nitride fiber layer preforms; then, the heat insulation layer skeleton slurry is injected between the two three-stage boron nitride fiber layers through the slurry injection holes provided on the side of mold one and / or mold two; then, mold one, mold two and the material in between are frozen. After freezing, a first-stage heating treatment is carried out in a nitrogen atmosphere; then a second-stage heating treatment is carried out, which is first heated in an ammonia and nitrogen atmosphere, and then carried out in a nitrogen atmosphere. Two layers of four-level boron nitride fiber are obtained with a three-dimensional mesh insulation layer skeleton sandwiched in the middle; the three-dimensional mesh insulation layer skeleton includes three-dimensional silicon nitride fiber; the thickness of the three-dimensional mesh insulation layer skeleton is 0.5~1.5cm; In a negative pressure environment, silica sol precursor is injected into the three-dimensional mesh insulation layer skeleton sandwiched between two layers of boron nitride fiber layers through the grouting holes set on the sides of mold one and / or mold two to obtain boron nitride composite fiber material precursor. The first stage of the heating process includes raising the temperature from room temperature to 80~120℃ under negative pressure, with a heating rate of 0.3~0.6℃ / min; The second stage of the heating process includes, in an atmosphere of ammonia and nitrogen, heating from 80-120℃ to 280-320℃ at a heating rate of 0.3-0.6℃ / min; heating from 280-320℃ to 580-620℃ at a heating rate of 0.5-2℃ / min; heating from 580-620℃ to 990-1000℃ at a heating rate of 5-10℃ / min; and holding at 990-1000℃ for 1-3 hours; the total flow rate of ammonia and nitrogen is 0.15-0.25 m³ / min. 3 / h; Then, heating is carried out in a nitrogen atmosphere, with the temperature increased from 990~1000℃ to 1550~1650℃ at a heating rate of 5.5~6.5℃ / min, and held at 1550~1650℃ for 1.8~2.2h; the nitrogen flow rate is 0.15~0.25m³ / min. 3 / h.
Citation Information
Patent Citations
External thermal insulation material and preparation method thereof
CN106584942A
Boron nitride fiber enhanced nitride composite material and preparation method thereof
CN109400173A